(untitled) (The International Journal for Scientific Research, 2026)
This study investigated the impact of S.A.Q (Speed, Agility, Quickness) exercises on agility, reaction time, and motor learning of badminton skills. An experimental design with two groups was applied to (30) first-year female students at Ashur University. The training program was implemented from November 2024 to March 2025. Results indicated statistically significant differences (P 0.05) in favor of post-tests, with the S.A.Q group showing superior performance in physical and skill-based variables. The study concludes that S.A.Q exercises significantly accelerate motor learning and enhance neuromuscular response.